Design, development and evaluation of a sullage treatment system - ARJUN GOPAKUMAR; Shajeer A. K. P; Soumya Rani T; Er. Asha Joseph (Guide) (Tavanur 2009 Kelappaji College of Agricultural Engineering and Technology)
Design, development and evaluation of a sullage treatment system
Design, development and evaluation of a sullage treatment system